The influence of job satisfaction, resilience and work engagement on turnover intention among village doctors in China: a cross-sectional study - Xuewen Zhang; Liyan Bian; Xue Bai; Dezhong Kong; Li Liu; Qing Chen; Ningxiu Li (BMC, 2020)
Abstract Background As the gatekeepers of rural residents' health, teams of village doctors play a vital role in improving rural residents' health. However, the high turnover of village doctors, both individually and collectively, threaten the stability of village medical teams. This research evaluated the influence of job satisfaction, resilience, and work engagement on the village doctors' turnover intention, and explored the mediating role of work engagement and resilience between job satisfaction and the turnover intention of village doctors in China. Methods A quantitative study using a self-administered questionnaire containing mostly structured items was conducted among village doctors with a sample size of 2693 from 1345 rural clinics in Shandong province, China, during May and June 2019. All variables including demographic characteristics, job satisfaction, resilience, work engagement and turnover intention were based on available literature, and measured on a 5- or 6-point Likert scale. Such statistical methods as one-way ANOVA, bivariate correlation, exploratory factor analysis (EFA), and Structural Equation Modelling (SEM) were used. Results Up to 46.9% of the subjects had a higher turnover intention and more than 26.3% of them had a medium turnover intention. The job satisfaction of village doctors could not only have a direct negative effect on turnover intention (β = − 0.37, p < 0.001), but also have an indirect effect through work engagement (β = − 0.04,=< 0.001). Meanwhile, work engagement also had a direct negative impact on turnover intention (β = − 0.13, p < 0.001), and resilience had an indirect negative impact on turnover intention through work engagement (β = − 0.09, p < 0.001). The above results of this study strongly confirmed that job satisfaction, resilience, and work engagement were early, powerful predicators of village doctors' turnover intention. Conclusion According to the results, the following should be taken seriously to improve job satisfaction: reasonable and fair income, effective promotion mechanism, fair social old-age security, reasonable workload, and strong psychological coping mechanisms for work stress. The turnover intention of village doctors could be reduced through improving job satisfaction, resilience and work engagement.